2009
DOI: 10.1890/08-0310.1
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses to fertilization recorded in tree rings: isotopic lessons from a long‐term fertilization trial

Abstract: Nitrogen fertilizer applications are common land use management tools, but details on physiological responses to these applications are often lacking, particularly for long-term responses over decades of forest management. We used tree ring growth patterns and stable isotopes to understand long-term physiological responses to fertilization using a controlled fertilization experiment begun in 1964 in Washington State (USA), in which three levels of nitrogen fertilizer were applied: 157, 314; and 471 kg/ha. Basa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
3
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 78 publications
6
53
3
1
Order By: Relevance
“…, ). This notion is supported by other studies which showed increased iWUE in Douglas‐fir due to nitrogen addition that likely increased photosynthesis relative to stomatal conductance (Brooks & Coulombe ; Brooks & Mitchell ). Our results also question whether an increase in absolute growth after density reduction on the dry site has resulted in higher tree vigour, that is, trees being further away from a tipping point, for example, drought‐related mortality (Reyer et al .…”
Section: Discussionsupporting
confidence: 74%
“…, ). This notion is supported by other studies which showed increased iWUE in Douglas‐fir due to nitrogen addition that likely increased photosynthesis relative to stomatal conductance (Brooks & Coulombe ; Brooks & Mitchell ). Our results also question whether an increase in absolute growth after density reduction on the dry site has resulted in higher tree vigour, that is, trees being further away from a tipping point, for example, drought‐related mortality (Reyer et al .…”
Section: Discussionsupporting
confidence: 74%
“…Brooks & Coulombe (2009) found similar short‐term dynamics in Δ 13 C cell as a result of fertilization in Douglas‐fir trees in Wind River, Washington. In that experiment, three different concentrations of nitrogen fertilization were used, and all three resulted in the same 1.5‰ decrease that was observed here in the fertilization‐alone treatment.…”
Section: Discussionmentioning
confidence: 55%
“…Tang et al (14) found increased WUE in both strip-bark and whole-bark bristlecone pines, whereas Graumlich (18) did not find evidence for a CO 2 fertilization effect as a cause for enhanced growth among subalpine conifers in the Sierra Nevada. It also should be noted that nitrogen inputs from human activity are enriching some western ecosystems (19), and long-term fertilization experiments suggest these inputs may be contributing to increases in tree growth (20). Our Approach to the Problem.…”
Section: Statement Of the Problemmentioning
confidence: 99%